(untitled) (Bangladesh Journal of Medical Science, 2011)
Aim: To evaluate the efficacy of transabdominal hydrosonography in the diagnosis of gastric carcinoma. Materials and Methods: Transabdominal hydrosonography of the stomach was carried out on fifty patients with clinical suspicion of gastric carcinoma. Endoscopic or peroperative biopsy was taken from pathological sites in all cases. The validity of transabdominal hydrosonography of the stomach was evaluated as compared to histopathological diagnoses. Results: The sensitivity, specificity, accuracy, positive predictive value and negative predictive value of transabdominal hydrosonography in the diagnosis of gastric carcinoma were 81.82%, 96.43%, 90.00%, 94.74% & 87.10% respectively. Conclusion: Transabdominal hydrosonography is a useful diagnostic modality for the diagnosis of gastric carcinoma. Key words: Gastric carcinoma, transabdominal hydrosonography. DOI: http://dx.doi.org/ 10.3329/bjms.v10i3.8360 BJMS 2011; 10(3): 170-176